Manajemen Komunikasi Pemasaran antara Lembaga Zakat (Amil) kepada Penerima Zakat (Mustahik) - Habib Ismail; Farid Aji Prakosa; Khusnul Amalin (Jurnal Simki Economic, 2025)
Indonesia has great potential in collecting zakat as a country with the largest Muslim population. However, its distribution is still predominantly consumptive and has not been optimal in improving the welfare of mustahik. This study aims to determine the marketing communication management carried out by the Indonesian Zakat Initiative (IZI) Yogyakarta in the "Lapak Berkah" program in collaboration with the Baitul Maal Foundation (YBM) PLN UP3 Yogyakarta. This program distributes productive zakat in the form of business capital assistance to mustahik. This study uses a descriptive method with a qualitative approach. Data analysis techniques are carried out through observation, interviews, and documentation to evaluate the effectiveness of the communication strategy implemented. The results of the study indicate that the marketing communication management implemented by IZI is effective in delivering the program to mustahik. Success factors include intensive communication, ongoing mentoring, and transparency in the selection process. This program not only provides financial assistance, but also equips mustahik with business skills, so that they can improve their standard of living. Overall, this program contributes to the transformation of mustahik into muzakki in the future through a sustainable productive zakat approach.